Highway drainage guidelines (American Association of State Highway and Transportation Officials, 2007)
The Highway Drainage Guidelines provides a consolidated overview of highway hydraulic design and discusses possible hydrology problems in the following areas: Hydraulic Considerations in Highway Planning and Location; Hydrology; Erosion and Sediment Control in Highway Construction; Hydraulic Design of Highway Culverts; The Legal Aspects of Highway Drainage; Hydraulic Analysis and Design of Open Channels; Hydraulic Analysis for the Location and Design of Bridges; Hydraulic Aspects in Restoration and Upgrading of Highways; Storm Drain Systems; Evaluating Highway Effects on Surface Water Environments; Highways Along Coastal Zones and Lakeshores; Stormwater Management; Training and Career Development of Hydraulics Engineers; Culvert Inspection, Material Selection, and Rehabilitation; Guidelines for Selecting and Utilizing Hydraulics Engineering Consultants.
The 4th edition of Highway Drainage Guidelines is in dual units and supersedes all previous versions, both metric and U.S. Customary units, of this title.
"Pub code: DS-HDG-4"--Page 4 of cover.
Keywords: Road drainage.; Hydraulic engineering.; elektronické knihy; electronic books